Unilateral biportal endoscopy via two different approaches for upper lumbar disc herniation: a technical note - Rongxue Shao; Weibin Du; Wei Zhang; Wei Cheng; Chengyue Zhu; Jiaming Liang; Jun Yue; Hao Pan (BMC Musculoskeletal Disorders, 2024)
Abstract Background The traditional surgical procedures for upper lumbar disc herniation (ULDH) usually lead to frequent complications. We aim to investigate the clinical efficacy of the unilateral biportal endoscopy (UBE) technique in treating upper lumbar disc herniation (ULDH). Methods From January 2020 to December 2021, the clinical data of 28 patients with ULDH treated with the UBE technique were collected and analyzed for surgery time under UBE, postsurgical drainage, postsurgical hospital stay, and complications. The clinical efficacy was evaluated according to the modified MacNab score, Oswestry disability index (ODI), and visual analogue scale (VAS) of low back pain and lower limb pain before the surgery; one week, one month, and three months after the surgery; and at the last follow-up. Results All patients underwent the UBE surgery successfully. The surgery time under UBE for non-fusion cases was 47.50 ± 11.84 min (monosegment) and 75.00 ± 20.66 min (two segments), while that for fusion cases was 77.50 ± 21.02 min. The postsurgical drainage for non-fusion cases was 25.00 ± 13.94 mL (monosegment) and 38.00 ± 11.83 mL (two segments), while that for fusion cases was 71.25 ± 31.72 mL. The postsurgical hospital stay was 8.28 ± 4.22 days. The follow-up time was 15.82 ± 4.54 months. The VAS score for each time period after the surgery was significantly lower (P < 0.05), while the ODI was significantly higher than that before the surgery (P < 0.05). According to the modified MacNab scoring standard, the ratio of excellent to good was 96.43% at the last follow-up. Two patients experienced transient numbness and pain in their lower limbs and no activity disorder after the surgery, and they recovered after conservative treatment. Conclusions The clinical effect of UBE technique in treating ULDH was reliable. According to the needs of the disease, the interlaminar approach or paraspinal approach of the UBE technique was selected. This technique took into account the effect of treatment, achieved the purpose of minimal invasiveness, and did not require special instruments. Therefore, it has the potential for clinical application.